Determinants of Third Party Funds of Islamic Commercial Banks in Indonesia - Annisa, Fayza Syahwa; Lina Nugraha Rani (Universitas Airlangga, 2024)
This research aims to analyse the influence of macroeconomic indicators and bank performance on Third Party Funds (DPK) of Islamic commercial banks in Indonesia during the period of 2018-2022, both partially and simultaneously. The macroeconomic indicators considered in this study are BI Rate, Gross Domestic Product (GDP), inflation, and exchange rate. The bank performance variables included in this study are Return on Asset (ROA), total assets (SIZE), and liquidity measured through the financing to deposit ratio (FDR). This research employs a quantitative method with panel data regression analysis technique. Sampling technique utilized purposive sampling, resulting in a sample of 12 banks. The best model obtained for this study is the common effect model (CEM). The results of this study indicate that partially, the BI Rate variable does not have a significant negative impact on DPK. Variables such as GDP, inflation, exchange rate, and ROA do not have a significant positive impact on DPK. However, total assets (SIZE) and liquidity have a significant positive impact on the DPK. Simultaneously, it shows that the independent variables have a significant influence on DPK.